1989
DOI: 10.1055/s-2007-1024900
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Blood Lactate Tests in Swimming*

Abstract: Three different modes of lactate tests were studied. Eleven male competitive swimmers performed the tests (n.100 m, n.300 m, 2.100m + 2.400 m) within 5 days. Swimming velocity (V) vs blood lactate (BLa) and V vs heart rate (HR) curves were averaged. In V vs BLa comparisons, the BLa values of 4 mmol.l-1 in 2.400 m, 3 mmol.l-1 in n.300 m, and 2 mmol.l-1 in n.100 m modes were found to correspond to the same V. Although the resting BLa values were similar before the testing occasions, the initial BLa value in very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
0
18
0
3
Order By: Relevance
“…Consequently, a lower Bla for a given v is possible and swimming in a 25-m pool would be less strenuous as compared to 50-m pool swimming. It should also be noted that exercise specific factors such as the duration of workload and whether the exercise was continuous or discontinuous could affect the Bla response to exercise [9,14,24,27,29,31]. This means that both lactate production and lactate accumulation accelerate as the exercise distance lengthens or resting intervals during exercise bouts shorten.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a lower Bla for a given v is possible and swimming in a 25-m pool would be less strenuous as compared to 50-m pool swimming. It should also be noted that exercise specific factors such as the duration of workload and whether the exercise was continuous or discontinuous could affect the Bla response to exercise [9,14,24,27,29,31]. This means that both lactate production and lactate accumulation accelerate as the exercise distance lengthens or resting intervals during exercise bouts shorten.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, each 200-m swim in the short course included more than a half less of stroking distance on each pool length before the next turn as compared to the long course. Keskinen et al [14] found that a slight increase of 0.5 mmol • l -1 in Bla concentration (2 mmol • l -1 level) in the n × 100-m test, 3 mmol • l -1 level in the n × 300-m test, and Bla of 4 mmol • l -1 in the 2 × 400-m test occurred at the same swimming velocity (v), which was considered a common reference point for these three exercise modes and the anaerobic threshold. In the heart rate (HR) vs. v comparison, the HR was higher in the n × 300 m and 2 × 400 m tests than in the n × 100-m test in the same v. In the HR vs. Bla comparison, the HRs were approximately the same at corresponding Bla values in the n × 100-m, n × 300-m, and 2 × 400-m tests.…”
Section: Discussionmentioning
confidence: 99%
“…The appropriateness of the training to the age group of the swimmers is one of the bases of the field of sports training [17].…”
Section: Introductionmentioning
confidence: 99%
“…O treinamento da endurance aeróbica tem a fi nalidade de aumentar a contribuição do metabolismo aeróbico (COS-TILL, 1991;ISSURIN, 2001;TREFFENE, 1981) permitindo uma velocidade de lactogênese diminuída. (CUNHA, 2000;ISSURIN, 2001;KESKINEN, 1989). Na natação, são utilizados com frequência dois protocolos para determinar a velocidade do treinamento: o primeiro proposto por Mader (1976) é um teste intervalado denominado de teste de duas velocidades (2V), que se caracteriza por nadar duas vezes 400 metros, sendo elas a 85% e 100% do tempo pessoal (NISHIBATA, 1993); e o segundo, um teste contínuo denominado T30 (OLBRECHT, 1984) que consiste em nadar 3000 metros de forma uniforme e constante a 100% da velocidade máxima para a distância (BABER, 1997).…”
Section: Introductionunclassified